Effects of erythropoiesis-stimulating agents on heart failure patients with anemia: a meta-analysis - Zhang, Hengliang; Zhang, Pei; Zhang, Yaheng; Yan, Junqiang; Dong, Pingshuan; Wang, Yanyu; Niu, Xiaowei (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction: Heart failure (HF) is always complicated with anemia and is associated with bad prognosis in this patient population. Several studies have assessed the potential role of erythropoietin-stimulating agent (ESA) in improving cardiac function and reducing the number of hospitalizations in anemic patients with HF. Aim : We performed a meta-analysis to assess the potential role of ESA in the treatment of anemic patients with HF. Material and methods : A literature and Medline search was performed to identify studies with control groups that examined the efficacy of ESA therapy in patients with HF and anemia. Results: A total of 11 studies were included (n = 3044 subjects) in the final analysis. Compared to placebo, ESA therapy was associated with increased hemoglobin levels (1.89 g/dl; 95% CI: 1.64–2.14, p < 0.00001), increased left ventricular ejection fraction (LVEF) to 6.88 (95% CI: 0.49–13.28, p = 0.03), decreased B-type natriuretic protein (–272.20; 95% CI: (–444.52)–(–99.89), p = 0.002), improvement in New York Heart Association functional class to –0.33 mean difference (95% CI: (–0.44)–(–0.23), p < 0.00001), and decreased hospitalization (OR = 0.61, 95% CI: 0.39–0.94, p = 0.02). There was no significant between-group difference in all-cause mortality (OR = 0.78, 95% CI: 0.51–1.21, p = 0.27). Conclusions : The treatment of anemia with ESA therapy did not reduce the rate of all-cause mortality among patients with heart failure, but ESA therapy made a potential important contribution to patients’ symptomatic improvement.